Application the Mike 3 model to simulate the turtibity dispersion due to sediment dumping activities in Nghi Son Port, Thanh Hoa Province - Nguyen, Hong Lan; Vu, Van Lan (Vietnam Journal of Marine Science and Technology, 2024)
The study applied the Mike 3 hydrodynamic model to simulate the turbidity propagation from sediment mud deposition activities at sea in the Nghi Son port area, Thanh Hoa province. The research results show that during the northeast monsoon period, the sediment mud concentration field is distributed southward from the deposition area, with sediment mud concentrations ranging from 0.01 kg/m³ to 0.4 kg/m³ within an influence radius of approximately 2.5 km. During the southwest monsoon period, the turbidity concentration distribution expands northward from the deposition area due to the influence of wind and currents during this season. The northern area of Nghi Son port is affected by the dispersion of turbidity concentrations below 0.04 kg/m³. The area surrounding Hon Me island has sediment mud concentrations ranging from 0.015 kg/m³ to 0.025 kg/m³. The turbidity concentration distribution with depth ranges from 0.01 kg/m³ to 0.4 kg/m³ and is primarily located at the seafloor depths ranging from -14 m to -18 m. The turbidity concentration gradually decreases towards the water surface. The turbidity concentration in the upper water layer is relatively low, ranging from 0.01 kg/m³ to 0.08 kg/m³, with depths from 0 to -5 m.